A Comparison of the Immunometabolic Effect of Antibiotics and Plant Extracts in a Chicken Macrophage-like Cell Line during a Salmonella Enteritidis Challenge - Giulia Giovagnoni; Famatta Perry; Benedetta Tugnoli; Andrea Piva; Ester Grilli; Ryan J. Arsenault (Antibiotics, 2023)
Immunometabolic modulation of macrophages can play an important role in the innate immune response of chickens triggered with a multiplicity of insults. In this study, the immunometabolic role of two antibiotics (oxytetracycline and gentamicin) and four plant extracts (thyme essential oil, grape seed extract, garlic oil, and capsicum oleoresin) were investigated on a chicken macrophage-like cell line (HD11) during a Salmonella Enteritidis infection. To study the effect of these substances, kinome peptide array analysis, Seahorse metabolic assay, and gene expression techniques were employed. Oxytetracycline, to which the bacterial strain was resistant, thyme essential oil, and capsicum oleoresin did not show any noteworthy immunometabolic effect. Garlic oil affected glycolysis, but this change was not detected by the kinome analysis. Gentamicin and grape seed extract showed the best immunometabolic profile among treatments, being able to both help the host with the activation of immune response pathways and with maintaining a less inflammatory status from a metabolic point of view.